Study of a sample of Dusky Groupers, Epinephelus marginatus (Lowe, 1834), caught in a tide pool at Lajes do Pico, Azores - Azevedo, José M. N. (1995)
A total of 175 juvenile Epinephelus marginatus (LOWE, 1834) (= E. guaza (LINNAEUS, 1758)) were collected in a 828 m2 tide pool at Lajes do Pico, Azores, confirming previous accounts on lhe unusual high density of that grouper in this area. All fishes were immature, with total lengths (TL) ranging from 4 to 36cm. Analysis of the length frequency distribution and scalimetry data suggest that four age classes are present: 0+ (4-7cm TL), 1+ (13-20cm TL). 2+ (18-25 cm TL) and 3+/4+ (one 36cm TL specimen). The length/weight relationship is given (TW=0.01388*TL^3.065) and compared with those from other geographical areas. The stomach contents varied with fish size: smaller groupers contained primarily small crustaceans (amphipods, crabs and isopods) while the larger groupers contained mainly larger crustaceans (shrimps and crabs) and fish. Present results suggest that the lagoon system of Lajes do Pico is a nursery for E. marginatus. Further studies are needed to evaluate the importance of this place to the grouper’s local stock and to provide a basis for its management and protection.